2010
DOI: 10.1186/1471-2229-10-54
|View full text |Cite
|
Sign up to set email alerts
|

Origins of the amphiploid species Brassica napus L. investigated by chloroplast and nuclear molecular markers

Abstract: BackgroundThe amphiploid species Brassica napus (oilseed rape, Canola) is a globally important oil crop yielding food, biofuels and industrial compounds such as lubricants and surfactants. Identification of the likely ancestors of each of the two genomes (designated A and C) found in B. napus would facilitate incorporation of novel alleles from the wider Brassica genepool in oilseed rape crop genetic improvement programmes. Knowledge of the closest extant relatives of the genotypes involved in the initial form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
147
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(163 citation statements)
references
References 21 publications
14
147
1
1
Order By: Relevance
“…We also confirmed that rutabagas had the main ptDNA haplotype (ptDNA haplotype 1), whereas asparagus kale had ptDNA haplotype 2. These results are also in agreement with the recent work of Allender and King (2010).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…We also confirmed that rutabagas had the main ptDNA haplotype (ptDNA haplotype 1), whereas asparagus kale had ptDNA haplotype 2. These results are also in agreement with the recent work of Allender and King (2010).…”
Section: Discussionsupporting
confidence: 94%
“…We analyzed different plastid regions than did Song and Osborn (1992), so this difference could reflect the idiosyncrasy of the B. montana chloroplast genome, which has local similarities with the other B. napus ptDNAs (Song and Osborn, 1992). Second, none of the accessions in our study had a B. oleracea ptDNA haplotype, which was represented only by the New Zealand Rawara accession in the Song and Osborn study; however, we found that this accession had only 18 chromosomes, suggesting that it belongs to the B. oleracea and not the B. napus germplasm (confirmed in Allender and King, 2010). Apart from these two points, our results confirmed the conclusions of Song and Osborn (1992).…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…Our findings support the previous findings that the origin of rapeseed occurs on more than one occasion (Song and Osborn, 1992;Allender and King, 2010), and that the C subgenome of rapeseed is related to cultivated B. oleracea (Olsson, 1954;Naughton, 1976;Song and Osborn, 1992;Gó mez-Campo and Prakash, 1999) or B. montana (Song and Osborn, 1992). In addition, our data suggest that the potential progenitors of the C subgenome of rapeseed can be extended to include other wild types, such as B. incana, B. bourgeaui, B. oleracea ssp.…”
Section: Discussionsupporting
confidence: 90%